Influence of the delivery systems using a microneedle array on the permeation of a hydrophilic molecule, calcein - Oh, Jae-Ho; Park, Hyoun-Hyang; Do, Ki-Young; Han, Manhee; Hyun, Dong-Hun; Kim, Chang-Gyu; Kim, Chang-Hyeon; Lee, Seung S.; Hwang, Sung-Joo; Shin, Sang-Chul; Cho, Cheong-Weon (European journal of pharmaceutics and biopharmaceutics, 2008)
Despite the advantages of drug delivery through the skin, such as easy accessibility, convenience, prolonged therapy, avoidance of the liver first-pass metabolism and a large surface area, transdermal drug delivery is only used with a small subset of drugs because most compounds cannot cross the skin at therapeutically useful rates. Recently, a new concept was introduced known as microneedles and these could be pierced to effectively deliver drugs using micron-sized needles in a minimally invasive and painless manner. In this study, biocompatible polycarbonate (PC) microneedle arrays with various depths (200 and 500 μm) and densities (45, 99 and 154 ea/cm 2) were fabricated using a micro-mechanical process. The skin permeability of a hydrophilic molecule, calcein (622.5D), was examined according to the delivery systems of microneedle, drug loading, depth of the PC microneedle, and density of the PC microneedle. The skin permeability of calcein was the highest when the calcein gel was applied to the skin with the 500 μm-depth PC microneedle, simultaneously. In addition, the skin permeability of calcein was the highest when 0.1 g of calcein gel was coupled to the 500 μm-depth PC microneedle (154 ea/cm 2) as well as longer microneedles and larger density of microneedles. Taken together, this study suggests that a biocompatible PC microneedle might be a suitable tool for transdermal drug delivery system of hydrophilic molecules with the possible applications to macromolecules such as proteins and peptides.